Response of Mustard Varities to Crop Geometry under Poplar in Terai region of Uttar Pradesh - Mohsin, Faiz; Mohsin, Afreen; Dhaka, S. S. (Indian Forester, 2021)
A field experiment was conducted on effects of crop geometry at farmer's field in District Pilibhit of Western Terai and Bhabar region of UTTAR PRADESH, India, during 2017- 2019. Three varieties of Mustard, viz; Goldi (V1), Ullahas (V2) and Pant pili sarson-1 (V3) were taken as treatments, four spacings, 40cm × 30cm (S1), 45cm × 20cm (S2), 30cm x 15cm (S3) and 20cm × 10cm (S4), with trees. The experiment was conducted in split plot design with 3-replications and repeated in rabi seasons for two consecutive years. The results revealed that the maximum seed yield was recorded in Pant pili st nd Sarson-1 (1648.0kg/ha and 2052.0kg/ha, respectively in (1st and 2nd year) followed by Goldi and Ullahas. Seed yield of Pant pili sarson-1 was also recorded highest in both the years 2 and 3 years under Poplar plantation (1542.0kg/ha and 1422.0kg/ha, respectively). The same pattern was also observed for stoveryield (kg/ha) in pure as well as in intercropped fields. Plant geometry significantly higher yield was st found in 40cm × 30cm (2241.0kg/ha and 2836.0kg/ha, respectively in 1st and 2nd) in Pant pili Sarson-1. The same pattern was observed in Goldi, followed by Ullahas. Similar results were also noticed in Mustard, grown with trees. Crop geometry (40cm × 30cm), observed the best in respect of number of primary branches/plant and seeds/siliqua, and it was also reflected on seed yield and Stover yield (kg/ha). The Pant pili Sarson-1 - of Mustard is highly suitable and recommended in Terai Region of UTTAR PRADESH due to its higher yield. So, wider spacing is suitable for Pant pili sarson-1; because of their bigger canopy.